THE ERMITAGE OF SANTA MARINA IN VILLAMARTÍN DE SOTOSCUEVA (BURGOS) AS A REFUGE FOR THE COMMUNITY. TO PROTECT A BUILDING WITH WRITINGS AND PAINTINGS IN 1456 (Estudios de Historia de España, 2023)
Marina was built by the council of Villamartín de Sotoscueva (Burgos) in 1456, according to the inscription painted on its apse. This paper states that this hermitage was built in a violent environment by the nobility's onslaught against the council powers, and the neighbourhood protected its interior and exterior with a series of surprising mural paintings of an apotropaic nature, as well as the roof, by means of a tile inscribed with verses from the Poem of Fernán González, contemporary to the building. All of this responds to concepts inscribed in the popular culture of the medieval imaginary, expressed through visual and written clues.
Keywords: Inscribed tile; Poema de Fernán González; Foundational inscription; Apothropaic; Visual Culture